In Women with Previous Pregnancy Hypertension, Levels of Cardiovascular Risk Biomarkers May Be Modulated by Haptoglobin Polymorphism - Andreia Matos; Alda Pereira da Silva; Maria Clara Bicho; Conceição Afonso; Maria José Areias; Irene Rebelo; Manuel Bicho (Obstetrics and Gynecology International)
Preeclampsia (PE) may affect the risk for future cardiovascular disease. Haptoglobin (Hp), an acute phase protein with functional genetic polymorphism, synthesized in the hepatocyte and in many peripheral tissues secondary of oxidative stress of PE, may modulate that risk through the antioxidant, angiogenic, and anti-inflammatory differential effects of their genotypes. We performed a prospective study in 352 women aged 35±5.48 years, which 165 had previous PE, 2 to 16 years ago. We studied demographic, anthropometric, and haemodynamic biomarkers such as C-reactive protein (CRP), myeloperoxidase (MPO), and nitric oxide metabolites (total and nitrites), and others associated with liver function (AST and ALT) and lipid profile (total LDL and cholesterol HDL, non-HDL, and apolipoproteins A and B). Finally, we study the influence of Hp genetic polymorphism on all these biomarkers and as a predisposing factor for PE and its remote cardiovascular disease prognosis. Previously preeclamptic women either hypertensive or normotensive presented significant differences in those risk biomarkers (MPO, nitrites, and ALT), whose variation may be modulated by Hp 1/2 functional genetic polymorphism. The history of PE may be relevant, in association with these biomarkers to the cardiovascular risk in premenopausal women.